2017
DOI: 10.1021/acs.macromol.7b01835
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Controlled Pillar[5]arene-Based Multiresponsive Supramolecular Polymer for Fluorescence Detection of Cyanide, Mercury, and Cysteine

Abstract: A simple and efficient approach to endow the controllable multi-stimuli-responsive property for the supramolecular polymer was successfully developed by rationally introducing iodine into a novel naphthalimide-functionalized pillar[5]­arene-based supramolecular polymer (PNA⊃GBP). Interestingly, by introducing iodine into the supramolecular polymer PNA⊃GBP, the iodine could not only control the optical properties and self-assembly states of PNA⊃GBP via electronic donor–acceptor effect but also control the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(57 citation statements)
references
References 52 publications
(87 reference statements)
0
56
0
Order By: Relevance
“…In recent years, more and more effort has been put into some sensors for sequential detection of ions . In particular, some metal complexes showed selectivity toward targeted anions in systems, such as Fe–HSO 4, Fe–F and Hg–I .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, more and more effort has been put into some sensors for sequential detection of ions . In particular, some metal complexes showed selectivity toward targeted anions in systems, such as Fe–HSO 4, Fe–F and Hg–I .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pillar[n]arenes, a new class of macrocyclic hosts, have been studied intensively since 2008 . Over the past ten years, pillar[n]arene derivatives are recognized as ideal building blocks for the construction of various supramolecular systems (supramolecular polymer gels, pseudorotaxanes, rotaxanes, supramolecular organic frameworks, supramolecular polymer networks, supramolecular hexagonal boxes and so on) .…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Compared with ion chromatography, 28 flow injection analysis 29 and titration analysis detection methods, 30 fluorescence method is simple, low cost and widely used. [31][32][33] In view of these and as part of our research interest in ions recognition, [34][35][36][37][38] herein, we reported a novel sensor molecule (HB1) based on 4-(diethylamino)-2-(hydroxy)-phenyl imine functionalized naphthalimide derivative (Scheme 1). Interestingly, the sensor molecule HB1 could not only fluorescence detection CNin DMSO/H 2 O (8 : 2, v/v) solution but also dual-channel (absorption and fluorescence) detection of Fe 3+ in DMSO solution with high selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%